If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y = 6 + x Solving 3y = 6 + x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '3'. y = 2 + 0.3333333333x Simplifying y = 2 + 0.3333333333x
| 2z-1=7 | | -4(2+2x)=4(3x+3) | | 5/6z=3/5 | | -14=x-17 | | 18-t=12 | | 2z-1=6 | | 5=6(q-15)-19 | | 48x-12x^2=0 | | 6-5x+5=11 | | 45=-6x+3 | | 2f+3=12 | | 36=(3)(2) | | 2y=27+y | | -5r+6r=-1 | | s/-100=-10 | | 2(w-4)-6w=4 | | 1/9-1/3 | | 2(h+1)-5=13 | | 7-6x+5x=-5 | | 6n-5=4-3n | | Y-3=-2+4 | | 3(6x+10)=129 | | 9=3p-5 | | 50+x=3x-2 | | 2/3=-8n | | (5-b)b=6 | | -(7y+3)-(-6y-6)=3 | | X-3=-3+2x | | (-5)=1/3(-4)+b | | 6a+1z= | | 3x-30=4+x | | -x+1+3x=4(x+2)-5 |